HIV and Schistosoma haematobium prevalences correlate in sub-Saharan Africa. - Ndeffo Mbah, Martial L; Poolman, Eric M; Drain, Paul K; Coffee, Megan P; van der Werf, Marieke J; Galvani, Alison P (Tropical medicine & international health : TM & IH, 2013)
Epidemiological studies have observed that genital schistosomiasis increases the risk of HIV infection in Africa. We analysed the correlation between Schistosoma haematobium prevalence and HIV prevalence across sub-Saharan African countries.
Keywords: Adolescent; Adult; Africa South of the Sahara; Animals; Circumcision, Male; Female; Genitalia; HIV; HIV Infections; Humans; Male; Middle Aged; Prevalence; Regression Analysis; Reproductive Tract Infections; Risk Factors; Schistosoma haematobium; Schistosomiasis haematobia; Young Adult